EFEKTIVITAS PENDEKATAN OPEN-ENDED DAN CTL DITINJAU DARI BERPIKIR KREATIF SISWA KELAS VII - Yeni Rahmawati ES (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2016)
This research aimed to describe the effectiveness of the open-ended and CTL approach in terms of creative thinking. This research was quasi-experimental study design with nonequivalent pretest-posttest design goup. The research population was all students in class VII SMP Negeri 1 Sekampung which consisted of five classes. The research sample consisted of two classes is determined randomly. First experimental group was treated the open-ended and experimental group II were treated CTL approach. The one sample t-test carried out to investigate the effectiveness of the open-ended and CTL approach. Data collection techniques used were tests. Engineering tests used to measure student creative thinking on basic competencies: 1) identify the properties of a rectangle, square, trapezoid, parallelogram, rhombus and a kite; 2) calculate the circumference and area of a rectangle up and use it in problem solving both before and after treatment. The results of the research show that the open-ended and CTL approach is effective in terms of creative thinking. Keywords: open-ended, contextual teaching and learning, creative thinking